(untitled) (Research, Society and Development, 2020)
Objective: Report the associated factors of exclusive breastfeeding for low weight newborns. Method: This is an integrative review, using journals in the databases: VHL and Scielo. Through exploratory reading, followed by selective reading, original and complete articles in the last five years were established as inclusion criteria. Excluding theses and dissertations, incomplete texts, editorial articles, abstracts, or publications outside the established period. Results and discussion: It was possible to verify that despite the various strategies to encourage exclusive breastfeeding for low weight newborns, such as the Human Milk Bank, Baby Friendly Hospital and the kangaroo method, many studies show that there is still a high percentage early weaning in Brazil, even in low birth weight infants. Some associated factors presented are maternal age, mother’s return to the labor market, cesarean delivery, use of pacifiers and other liquids before the age of six months. Conclusion: Exclusive breastfeeding is essential for improving the health conditions of the newborn. Factors ranging from the type of delivery to the incentive by the health team can contribute to maintaining this breastfeeding. The importance of further studies on the effective methods of incentive and main reasons that lead to early weaning is highlighted.